Morphology Related Defectiveness in ZnO Luminescence: From Bulk to Nano-Size - Roberta Crapanzano; Irene Villa; Silvia Mostoni; Massimiliano D’Arienzo; Barbara Di Credico; Mauro Fasoli; Roberto Scotti; Anna Vedda (Nanomaterials, 2020)
This study addresses the relationship between material morphology (size, growth parameters and interfaces) and optical emissions in ZnO through an experimental approach, including the effect of different material dimensions from bulk to nano-size, and different excitations, from optical sources to ionizing radiation. Silica supported ZnO nanoparticles and ligand capped ZnO nanoparticles are synthesized through a sol–gel process and hot injection method, respectively. Their optical properties are investigated by radioluminescence, steady-state and time-resolved photoluminescence, and compared to those of commercial micrometric powders and of a bulk single crystal. The Gaussian spectral reconstruction of all emission spectra highlights the occurrence of the same emission bands for all samples, comprising one ultraviolet excitonic peak and four visible defect-related components, whose relative intensities and time dynamics vary with the material parameters and the measurement conditions. The results demonstrate that a wide range of color outputs can be obtained by tuning synthesis conditions and size of pure ZnO nanoparticles, with favorable consequences for the engineering of optical devices based on this material.